Electronic structure of PbSnS₃ and PbGeS₃ semiconductor compounds with the mixed cation coordination - Bletskan, M.M.; Bletskan, D.I.; Kabatsii, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The self-consistent band structure calculation of PbSnS₃ and PbGeS₃ ternary compounds with the mixed cation coordination was performed using the ab initio density functional theory method. It has been found that both compounds are indirect-gap semiconductors. The calculated band-gap widths are Egi = 0.75 eV for PbSnS₃ and Egi = 1.96 eV for PbGeS₃. It was performed the analysis of partial contributions to the total density of electronic states, which allowed to identify the genetic nature of valence and conduction bands. The feature of the structure of occupied energy bands in these compounds is the presence of isolated quasi-core d-band of lead atoms and the contribution of Pb6s-states of lone-electron pair to the top of valence band as well as to the second occupied subband. The electron density maps in the different planes have been analyzed. They clearly demonstrate presence of covalent-ionic bond character within the infinite chains and ribbons with prevailing charge concentration on Ge–S, Sn–S, Pb–S bonds, and a weak van der Waals bond component with participation of lone-electron pair of lead between layers as well as ribbons.